Therapeutic targeting of histone H3 lysine 36 trimethylation-deficient cancers - Lopez, K (2019)
Histone modifications play diverse and essential roles in the maintenance of genome integrity, as evidenced by the frequency at which different histone marks are dysregulated during tumourigenesis. The trimethylation of histone H3 at lysine 36 (H3K36me3) and SETD2, the enzyme solely responsible for this histone mark, are important in many cellular processes and have been reported to be lost or mutated in cancers. Targeting cells that are deficient in H3K36me3 or SETD2 is therefore an attractive therapeutic strategy for specifically killing tumour cells with minimal effect on normal tissue using the concept of synthetic lethality. Using a previously reported synthetic lethal interaction between SETD2 and the WEE1 kinase as a starting point, a high-throughput small-molecule compound screen was performed in cells in which SETD2 had been deleted using CRISPR-Cas9 technology. The aim of this screen was to identify two categories of hits: (1) those that enhance the SETD2-WEE1 synthetic lethality (synergy hits) and (2) those that target SETD2-CRISPR cells on their own (novel synthetic lethality hits). Analysis of the synergy hits focused on histone deacetylases (HDACs), which revealed that the Class I HDACs HDAC1 and HDAC2 had differential effects on the SETD2-WEE1 synthetic lethality. Furthermore, depletion of both HDACs individually led to a significant loss of viability specifically in SETD2-CRISPR cells. The results suggest a putative synthetic lethality between SETD2 and HDAC2 that bears certain similarities to the relationship between SETD2 and WEE1. The most potent among the novel synthetic lethality hits was a compound called RITA, which demonstrated the ability to target SETD2 deficiency in the form of CRISPR knockout, siRNA knockdown, and naturally occurring mutations. This was accompanied by a striking upregulation and activation of the p53 tumour suppressor, activation of the DNA damage response, cell cycle arrest, and apoptosis. These phenotypes were further associated with increased levels of replication stress markers and reduced replication fork velocity. The potential mechanism of action of this compound was investigated via a number of strategies based on current knowledge of SETD2 and RITA, as well as more exploratory approaches. Overall, the data indicate that perturbations in the G1/S transition and replication stress play key roles in mediating RITA’s cytotoxicity in the context of SETD2 loss.